INKULTURASI IMAN KRISTEN DALAM BUDAYA TORAJA: STUDI TEOLOGIS TERHADAP MAKNA RAMBU SOLO’ DAN RAMBU TUKA’ DALAM KONTEKS IMAN DAN PENDIDIKAN AGAMA KRISTEN - Sartika Sulle Padang; Desi Sesa, Agustina Pince Manaruri, Alimut kenangalem, Helena Wombaibabo (ADISAM PUBLISHER, 2025)
Toraja culture has a rich tradition, especially in the Rambu Solo' (funeral) and Rambu Tuka' (thanksgiving) ceremonies. Both of these ceremonies reflect the community's beliefs in the cycle of life, relationships with ancestors, and expressions of gratitude. With the entry of Christianity into Toraja, a process of inculturation occurred, in which elements of local culture were integrated into religious practices. The church played an important role in reinterpreting the meaning of these traditions to align with Christian teachings. This effort is seen in the use of tongkonan architecture for churches, spiritual songs in the Toraja language, and the reinterpretation of offerings in traditional ceremonies. This study uses a field study method to explore how the Toraja people maintain their culture while practicing the Christian faith. The results show that inculturation can be a bridge between culture and faith without eliminating the essential values of both